Implementation of Congregational Duha and Zuhur Prayers as an Effort to Discipline Students - Nadila, Miftachul; Romelah, Romelah; Khurin Maknin, Nur Afifah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The purpose of the study is to explain the implementation of Duha prayer and zuhur prayer in the congregation as an effort to discipline students at SMK Muhammadiyah 2 Malang. This study uses a qualitative method with a case study approach. The data collection technique uses participatory observation, interviews, and documentation. Data was obtained from two PAI teacher informants, student affairs officers, and three student informants. Meanwhile, data analysis using the theory of Miles, Huberman, and Saldana was carried out through three stages, namely data condensation, system display, and conclusion drawn. The results of the study show that the implementation of Duha and zuhur prayer activities at SMK Muhammadiyah 2 Malang has gone well even though there are still some students who need direction or control from picket teachers as well as the limitations of time and place of ablution which cause students to be late or even not participate in congregational prayers.